Gas exchanges and morphometric measurements of a variety of hops (Humulus lupulus L.) (Cannabaceae) grown in subtropical conditions under organic and conventional management - Neves, Caio [UNESP]; Aires, Eduardo [UNESP]; Fortuna, Gabriel [UNESP]; Campos, Olivia [UNESP]; Gomes, Jordany [UNESP]; Ono, Elizabeth [UNESP]; Rodrigues, João [UNESP]; Bonfim, Filipe [UNESP] (Southern Cross Publishing, 2023)
Hops are native to the Northern Hemisphere and are widespread throughout the world; in Brazil, crops are grown on a small scale. How management differentiation can affect the physiological development of crops in subtropical climates is not well studied. The objective of this study was to evaluate the physiological and morphometric performance of five hop varieties under organic and conventional management. These experiments were conducted at Lageado Farm, at the campus of Sao Paulo State University in Botucatu. A 2 x 5 factorial design was adopted, with the main factor being the cultivation system (organic and conventional) and the secondary factor being the hop varieties (Cascade, Columbus, Chinook, Hallertau Mittelfrüeh and Nugget). The cultivation systems differed by fertilization and phytosanitary management. Analyses of gas exchange and chlorophyll a fluorescence were performed during the vegetative development of the plants and during branch elongation. Morpho metric analyses of the plants were performed to determine the number of internodes (22.40; 18.20) and the heights of the plants (201.09; 131.07), with organic and conventional treatment, respectively. All the varieties showed satisfactory physiological and morphometric performance; however, plants grown under organic management had better results than those grown under the conventional cropping system. Lastly, we measured the potential efficiency of PSII; Hallertau M. (0.89), Nugget (0.89) and Columbus (0.88) presented the highest measurements, and the lowest values were observed in Cascade (0.86) and Chinook (0.85). In general, Hallertau M. and Columbus had the highest gas exchange values, while Cascade had the lowest.
Keywords: Acclimatization; photosynthetic performance; production systems; tropicalization; vegetative performance